The effect of SiC decomposition on microstructure of Ni3Al - Guler, O.; Evin, E.; Yilmaz, O.; Guler, S. H. (Natl Inst Optoelectronics, 2015)
The intermetallic matrix composites (IMCs) of Ni3Al reinforced by SiC were fabricated by powder metallurgical routes via solid state reaction of nickel and SIC particulates by volume combustion process. Pure nickel, aluminum and SIC powders were used as initial substances. The powders were mixed, and the compacts were combusted in an atmosphere controlled furnace. The synthesis of the SiC added Ni3Al was attempted to improve the nature of the Ni3Al composite. The initially added SIC particles were unstable and decomposed partially within the matrix during combustion, and the morphology of the IMCs changed upon the dissolution rate of SIC and combustion temperature. It was confirmed that the dissolution rate of SIC was effective on improvement of the hot working temperature of Ni3Al IMCs.
Keywords: Ni3Al; Intermetallics; Reaction sintering; Combustion synthesis